2017
DOI: 10.25066/agrotec.v38i3.29919
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada associada à inoculação com <i>Azospirillum brasilense</i> na cultura do milho

Abstract: Resumo -A adubação nitrogenada por fertilizantes minerais é um dos principais manejos utilizados pelos produtores como forma de suprir as necessidades das plantas com esse nutriente. O objetivo foi avaliar o efeito da adubação nitrogenada sobre o crescimento de plantas híbridas de milho associadas com bactérias diazotróficas endofíticas. O experimento foi conduzido em casa de vegetação, por um período de 90 dias, com substrato natural. O delineamento experimental utilizado foi em blocos casualizados, sendo que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…30, 2.35, and 2.46 m, respectively (Table 1). This increase in height specificallyrelates to the effects that nitrogen promotes on cell division, plant metabolism, and photosynthetic processes (Morais et al, 2017).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…30, 2.35, and 2.46 m, respectively (Table 1). This increase in height specificallyrelates to the effects that nitrogen promotes on cell division, plant metabolism, and photosynthetic processes (Morais et al, 2017).…”
Section: Resultsmentioning
confidence: 89%
“…The DM content is usually related to the age of the plant, therefore older plants will produce high DM content with low digestibility such as lignin, cellulose, hemicellulose, and other nutritional components (Burin, 2018). In an experiment carried out by Morais et al (2017), it was observed that DM of leaves and stems had a significant effect with N fertilization in corn, unlike the combination of N with inoculation, with no statistic effect. There was also no statistically significant effect of inoculation via seed, sowing furrow, and leaf on the total dry matter of corn (Andrade et al, 2019).…”
Section: /12mentioning
confidence: 99%
See 1 more Smart Citation
“…However, inoculation benefits were higher (+21%) at yields lower than 3000 kg ha -1 and at lower N rates (≤ 50 kg ha -1 , +8%). Such differences in response to maize inoculation can also be attributed to factors such as the number of viable cells per seed, the cell viability, the plant genotype, the Azospirillum genus, the inoculant physical placement, the biochemical characteristics and competition with other microorganisms native to the soil [30,31].…”
Section: Field Experimentsmentioning
confidence: 99%